2018
DOI: 10.1088/1475-7516/2018/09/015
|View full text |Cite
|
Sign up to set email alerts
|

Generalized uncertainty principle, black holes, and white dwarfs: a tale of two infinities

Abstract: It is often argued that quantum gravitational correction to the Heisenberg's uncertainty principle leads to, among other things, a black hole remnant with finite temperature. However, such a generalized uncertainty principle also seemingly removes the Chandrasekhar limit, i.e., it permits white dwarfs to be arbitrarily large, which is at odds with astrophysical observations. We show that this problem can be resolved if the parameter in the generalized uncertainty principle is negative. We also discuss the Plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
120
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 52 publications
13
120
0
Order By: Relevance
“…Such a choice of sign of α may seem unusual, but it is consistent with some quantum gravity models in which physics at the Planck scale "classicalized" and becomes deterministic (as the RHS of the GUP equation goes to zero when ∆p · c is equal to the Planck energy) [13][14][15][16]. Specifically, we have seen that a lattice "spacetime crystal" gives rise to such a GUP [13].…”
Section: Introduction: the Issue With Temperature Of Black Hole Resupporting
confidence: 80%
See 3 more Smart Citations
“…Such a choice of sign of α may seem unusual, but it is consistent with some quantum gravity models in which physics at the Planck scale "classicalized" and becomes deterministic (as the RHS of the GUP equation goes to zero when ∆p · c is equal to the Planck energy) [13][14][15][16]. Specifically, we have seen that a lattice "spacetime crystal" gives rise to such a GUP [13].…”
Section: Introduction: the Issue With Temperature Of Black Hole Resupporting
confidence: 80%
“…(1), we would find that there is no lower bound for black hole mass, so in principle the black hole can evaporate completely. However the final temperature is finite and nonzero [14,15], also see Fig. (1).…”
Section: Introduction: the Issue With Temperature Of Black Hole Rementioning
confidence: 83%
See 2 more Smart Citations
“…Ostriker and his collaborators first showed that rotation (and also magnetic field) of the white dwarf can lead to the violation of the Chandrasekhar mass limit (Ostriker & Hartwick 1968), but they could not reveal any limiting mass. More recently, magnetic field (Das & Mukhopadhyay 2013, 2015aSubramanian & Mukhopadhyay 2015), modified theories of gravity (Das & Mukhopadhyay 2015b;Kalita & Mukhopadhyay 2018;Carvalho et al 2017), generalized Heisenberg uncertainty principle (Ong 2018) etc. have been proposed as some of the prominent possibilities to explain super-Chandrasekhar white dwarfs and also corresponding limiting mass.…”
Section: Introductionmentioning
confidence: 99%